Duloxetine in Psychiatric Disorders: Expansions Beyond Major Depression and Generalized Anxiety Disorder - Muscatello, Maria Rosaria Anna; Zoccali, Rocco A.; Pandolfo, Gianluca; Mangano, Paolo; Lorusso, Simona; Cedro, Clemente; Battaglia, Fortunato; Spina, Edoardo; Bruno, Antonio (Frontiers in Psychiatry, 2019)
Abstract Introduction: Duloxetine hydrochloride (DUL) is an antidepressant included in the pharmacological class of serotonin-norepinephrine reuptake inhibitors approved for the treatment of Major Depressive Disorder, Generalized Anxiety Disorder, Diabetic Peripheral Neuropathic Pain, Fibromyalgia, Chronic Musculoskeletal Pain, and, in Europe, also for treating Stress Urinary. The aim of this review was to elucidate current evidences on the off-label use of DUL in the treatment of a variety of psychiatric disorders. Methods: Literature searches were conducted until September 2018, in main biomedical search engine databases. Search terms used for the topic were as follows: “persistent depressive disorder” AND/OR “dysthymic disorder”, “bipolar depression”, “seasonal affective disorder”, “obsessive-compulsive disorder”, “social phobia”, “panic disorder”, “posttraumatic stress disorder”, “schizophrenia”, “eating disorders”, “sexual disorders”, “personality disorders”, AND “duloxetine”. Article titles and abstracts were scanned to determine relevance to the topic. For additional studies, the Authors also examined the reference lists of several of the included papers. Results: The evidence suggests that the efficacy of DUL has been proven in the Pure Dysthymic Disorder of older adults and in the Seasonal Affective Disorder, with relatively high rates of response and remission, and in Post-Traumatic Stress Disorder, a disorder in which both serotonergic and noradrenergic dysfunctions, probably related with the core symptoms of the disease (conditioned-fear responses), have been demonstrated. Conclusion: The majority of evidence comes from open-label studies, limited by short trial duration, small sample sizes, and by the lack of control groups; furthermore, the long-term efficacy of DUL has not yet been investigated. This relative paucity of data does not allow to draw firm conclusions on the potential role of DUL in the treatment of psychiatric disorders other than MDD and GAD; further randomized, placebo-controlled studies of adequate duration on larger samples are needed for better defining the whole therapeutic potential of this antidepressant.